DNA Barcoding Tanaman Mangga Kasturi (Mangifera casturi) Asal Kalimantan Selatan Berbasis DNA Kloroplas Gen rbcL dan matK - Sogandi Sogandi; Zuraida Sagala (Fakultas Farmasi Universitas Pancasila, 2022)
This study aims to see the genetic diversity of the musk mango (Mangifera casturi) plant in South Kalimantan based on DNA barcode techniques using sequences from the rbcL gene and the matK gene. The plant samples used in this study were the leaves of the musk mango (Mangifera casturi) taken from eight regencies and cities in South Kalimantan Province, namely from Amuntai, Astambul, Barito Kuala, Peat, Kandanga, Babirik, Tabalong, and Tanah Laut. Isolation and DNA analysis of the musk mango plant was carried out in the research laboratory of the Faculty of Biotechnology, Atma Jaya Catholic University of Indonesia, Jakarta. The analysis of the genetic diversity of the musk mango began with the stage of amplifying genomic DNA (gDNA) using rbcL and matK primers. The results of the DNA isolation samples showed a high concentration level of 17-91 ng/µL with a purity of 1.72 -1.92 ng/µL. When PCR was carried out using rbcL and matK primers, from 8 areas in South Kalimantan, 5 samples (Babirik, Tabalong, Kandangan, Amuntai, Batola, Peat, and Tanah Laut) were amplified with rbcL primers and 6 samples (Tanah Laut, Babirik, Tabalong , Amuntai, Peat, and Kandangan) amplified with matK primer. The relationship between the musk mango in South Kalimantan can be seen from the phylogenetic tree.